SISTEMA DE CERTIFICAÇÃO PROFISSIONAL POR COMPETÊNCIA: UM MODELO EM CONSTRUÇÃO PARA O BRASIL - Souza, Maria Regina Alves de (2006)
This work has as main objective to present a proposal of construction of a Brazilian professional certification system for competences, that the rise of the citizens scholarship promotes, allowing the continuity of studies, articulated with the diverse existing Brazilian experiences, and that is an instrument of social inclusion of the worker in the work market. This proposal, of exploratory and descriptive character, was conceived on the basis of national experiences, in the analysis of professional certification models of the International Organization of Work - OIT, and of countries of the European Union, whose organization was stimulated by the social actors. Documental and bibliographical research was developed jointly with field study, in which data were collected through an interview with a semi structuralized script and participant observation. The relevance of this research is due to its contribution of proposing the construction of a Brazilian professional certification system harmonized to international practices, that optimizes the application of resources and values the diversity of professional certification existing experiences in Brazil. The study allowed to identify points of improvement in the model considered, as well as supply informatoins to become the model most efficient and capable to reach the purposes proposals. In the end of the work recommendations for the accomplishment of new studies are made